State civil services training in India - Goyal, Rajni (Jaipur, 1988)
With the growing acceptance of training as an effective instrument of human resource development in civil services and with its manifest impact on enhancing individual and organizational effectiveness, the literature on civil service training in India has proliferated recently. However, most of the studies on the subject focus on the Central level adminis trative services, and more particularly on the All India Services.
Keywords: Civil service-India